2009
DOI: 10.1186/1472-6882-9-29
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of HIV-1 entry by extracts derived from traditional Chinese medicinal herbal plants

Abstract: Background: Highly active anti-retroviral therapy (HAART) is the current HIV/AIDS treatment modality. Despite the fact that HAART is very effective in suppressing HIV-1 replication and reducing the mortality of HIV/AIDS patients, it has become increasingly clear that HAART does not offer an ultimate cure to HIV/ AIDS. The high cost of the HAART regimen has impeded its delivery to over 90% of the HIV/AIDS population in the world. This reality has urgently called for the need to develop inexpensive alternative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…A number of herbal medicines were shown, in both in vitro and in vivo experiments, to possess anti‐HIV properties (Liu, ; Park et al , ). However, a randomized, placebo‐controlled clinical trial of Chinese herbal drugs failed to show this effect (Weber et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of herbal medicines were shown, in both in vitro and in vivo experiments, to possess anti‐HIV properties (Liu, ; Park et al , ). However, a randomized, placebo‐controlled clinical trial of Chinese herbal drugs failed to show this effect (Weber et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these plantsderived antiretroviral therapies have been shown to have inhibitory activities against several HIV-1 processes, including viral entry, reverse transcription, replication, integration, virus maturation and virion budding. Some of these compounds have been clinically tested, with favourable results (Asres et al, 2005;Park et al, 2009;Vo and Kim, 2010;Jiang et al, 2010;Filho et al, 2010;Sing and Bodiwala, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, pre-treatment of the reporter virus with the extract and post-infection treatment had little effects on the infectivity or gene expression of the reporter virus. These results demonstrated that the extract inhibits HIV-1 replication likely by blocking HIV-1 interaction with target cells, i.e., the interaction between gp120 and CD4/CCR5, or gp120 and CD4/CXCR4, and points to the potential of developing the extract as HIV-1 entry inhibitors [24].…”
mentioning
confidence: 91%